2006
DOI: 10.1016/j.trstmh.2005.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound verification of bladder damage is associated with known biomarkers of bladder cancer in adults chronically infected with Schistosoma haematobium in Ghana

Abstract: Long-term infection with urinary schistosomiasis has been associated with development of bladder cancer. However, bladder cancer is difficult to diagnose without invasive measures such as cystoscopy, thus there is little information on the epidemiological extent of the problem. Studies have been either case-control studies or case examinations in different geographical areas, estimating a schistosome-associated bladder cancer incidence of 3-4 cases per 100,000. We have used three indicators to examine the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 25 publications
6
46
0
1
Order By: Relevance
“…The epidemiological association between SCC of the bladder with schistosomiasis haematobia is based both on case control studies and on the correlation of bladder cancer incidence with prevalence of S. haematobium infection within diverse geographic locations. The incidence of urogenital schistosomiasis-associated SCC is estimated in 3-4 cases per 100 000 [34]. Schistosomiasis haematobia is a chronic infection.…”
Section: Urogenital Schistosomiasismentioning
confidence: 99%
“…The epidemiological association between SCC of the bladder with schistosomiasis haematobia is based both on case control studies and on the correlation of bladder cancer incidence with prevalence of S. haematobium infection within diverse geographic locations. The incidence of urogenital schistosomiasis-associated SCC is estimated in 3-4 cases per 100 000 [34]. Schistosomiasis haematobia is a chronic infection.…”
Section: Urogenital Schistosomiasismentioning
confidence: 99%
“…The severity and frequency of the sequelae of urinary schistosomiasis and of its complications (urothelial cancers) depend on the intensity of infection (worm burden and tissue egg burden) and the duration of infection (Hodder et al, 2000;Herrera et al, 2005). A S. haematobium-associated bladder cancer incidence of 3-4 cases per 100,000 has been estimated (Shiff et al, 2006). Felix et al (2008) showed that the occurrence of transitional cell carcinoma (TCC) of the bladder has supplanted SCC in Egypt following a major decline in the prevalence of urinary schistosomiasis.…”
Section: Introductionmentioning
confidence: 99%
“…Lesions in urinary tract caused by S. haematobium in sub-Saharan Africa are characterized by signs and symptoms like haematuria, dysuria and hipogastralgy, and in advanced stages can evolve to cancer [6,7]. Ultrasound analysis permits the detection of alterations of urinary tract, kidneys (hydronephrosis), as well as lesions and presence of “sandy patches” in the vesical wall [1,7,8]. …”
mentioning
confidence: 99%